Air kelapa dan air buah lontar sebagai modifikasi pengencer alternatif pada semen babi landrace - Christin Y. L. Mere; Cynthia D. Gaina; Nancy D. F. K. Foeh (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
The objective of this study was to determine the capability of coconut water, coconut water-honey, palmyra juice, palmyra juice-honey in maintaining sperm motility and viability of landrace boars during storage at refrigerator (5 °C ) and room temperature (32 °C). This experiment used a completely randomized design (CRD) with 8 treatments and 3 replications. Semen was collected twice a week from landrace boars. Semen Characteristics and their quality were evaluated macroscopically and microscopically. Good quality semen have motility >70%, sperm concentration >200x106 sperm/ml and morphological abnormalities less than 20%, these semen were added with Coconut Water (P1), Coconut Water-Honey (P2), palmyra juice (P3) and palmyra juice-honey (P4). Sperm motility and viability were evaluated every 2 hours until 40% motility were evaluated. The results showed that fresh semen characteristics were good, with the presentage of sperm motility 85%, sperm concentration 266.67 ± 13.33% and morphological abnormalities 12.67±2.90%. The best diluent stogare at 5 °C was palmyra juice-honey better than palmyra juice, coconut water and coconut water-honey with sperm motility 55.70±7.63%during 28 hours observation. The best dilluent storage at 32 °C was palmyra juice with sperm motility 46.67±6.66% during 18 hours observation. In conclusion that palmyra juice-honey and palmyra juice effective to maintain semen quality of landrace boars during preservation